Muscular request of different fin uses - Gouvernet, G.; Rao, G.; Barla, C.; Baly, L.; Grelot, L.; Berton, E. (Biomechanics and Medicine in Swimming XI, 2010)
The purpose of the present study was to examine the muscular request of different practices using different fins. We focused on three different fin uses: body-board, swimming, and snorkelling. We used inverse dynamics to estimate the muscular power of the lowers body joints (knee and hip). For each practice we recorded the three-dimensional kinematics of lower limbs with underwater camcorders. The input forces and torques measurement, necessary for bottom-up inverse dynamic, were measured by a twice fin robot which reproduced mean foot kinematics of each practice recorded before. The three kinematics and joint power computed at knee and hip were analysed. Kinematics differs for each practice but joint powers are statically the same (1,87±1,54 W/Kg). This method has the main advantage to allow us to characterize precisely effect of fin blade on human joints.